THE INCREASED NUMBER OF EPITHELIAL CELLS DETACHED FROM ORAL MUCOSA BECAUSE OF AMALGAM FILLINGS: PENINGKATAN JUMLAH SEL EPITELIUM TERLEPAS PADA MUKOSA ORAL AKIBAT TAMBALAN AMALGAM - Primasari, Ameta; Sitompul, Safriani (TALENTA, 2017)
Amalgam is a filler material containing toxic mercury. One of the main risks comes from the mercury vapor released in the mouth. The presence of amalgams in the oral cavity changes the metabolism of epithelial cells in the oral mucosa. Exfoliative cytology is a fast and easy method because the examination is only performed on the surface of the oral mucosa, and epithelial cells can be released without anesthesia. The research method was an analytical descriptive with a cross-sectional design. Epithelial cells from oral mucosa were collected from 32 samples using the cytobrush method. The epithelial cells were collected on the closest buccal mucosa of the amalgam restoration. The number of epithelial cells in the oral mucosa was seen through micrographs from a microscope with 100x magnification. The data were analyzed using the Mann Whitney U test to determine the number of epithelial cells released. The Mann Whitney U test results showed that there was a significant difference in the number of oral mucosal epithelial cells obtained ​​between subjects with amalgam and subjects without amalgam with p<0.05. In addition, there was a difference in the features of oral mucosal epithelial cells between subjects with amalgam and subjects without amalgam. In conclusion, the number of epithelial cells obtained from amalgam users was higher than the subjects without restorations. The forms of epithelial cells which experience desquamation in the subjects with amalgam were more irregular than those of subjects without restorations.